(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Amelína S. M. Preparation of teachers of agrarian universities for dialogue of pedagogical process. The article discusses the principles of dialogic learning and training of teachers of agricultural universites. It is proved that the use of dialogue in the classroom depends on the willingness of teachers as one of the main parts of the educational process. A program of psychological and pedagogical workshops for teachers of agricultural universites «Dialogue in teaching» is proposed.